Agency and Anxiety: Delusions of Control and Loss of Control in Schizophrenia and Agoraphobia - Gallagher, Shaun; Trigg, Dylan (Frontiers in Human Neuroscience, 2016)
We review the distinction between sense of agency and sense of ownership, and then explore these concepts, and their reflective attributions, in schizophrenic symptoms and agoraphobia. We show how the underlying dynamics of these experiences are different across these disorders. We argue that these concepts are complex and cannot be reduced to neural mechanisms, but involve embodied and situated processes that include the physical and social environments. We conclude by arguing that the subjective and intersubjective dimensions of agency and ownership cannot be considered in isolation from one another, but instead form an interdependent pairing.